Pursestring Closure versus Conventional Primary Closure Following Stoma Reversal to Reduce Surgical Site Infection Rate. Issue 8 (August 2015) - Hsieh, Meng-Chiao; Kuo, Liang-Tseng; Chi, Ching-Chi; Huang, Wen-Shih; Chin, Chih-Chien
<x xml:space="preserve">Abstract</x> BACKGROUND: Stoma reversal is a surgical procedure commonly used following temporary defunctioning stoma surgery. Surgical site infection is one of the most common postoperative morbidities. A few skin closure methods have been developed to decrease surgical site infection. However, the optimal skin closure method is still in debate. OBJECTIVE: The aim of this study was to compare the surgical site infection rate and other postoperative outcomes between the pursestring closure and conventional primary closure techniques. DATA SOURCES: We searched the MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials for relevant trials. STUDY SELECTION: We conducted a meta-analysis of randomized controlled trials that compared the surgical outcomes following pursestring closure and conventional primary closure techniques. INTERVENTION: We conducted the meta-analysis by using the random-effects model. MAIN OUTCOME MEASURES: The primary outcome of interest was surgical site infection following stoma reversal within 30 days after operation. RESULTS: This meta-analysis included 4 randomized controlled trials with a total of 319 participants (162 in the pursestring closure group and 157 in the conventional primary closure group). Compared with the conventional primary closure group, the pursestring closure group had a significant decrease in surgical site infection (risk difference, –0.25; 95% CI, –0.36 to –0.15; p < 0.00001; number needed to treat = 4) and higher satisfaction with cosmetic outcomes (standard mean difference, 0.7; 95% CI, 0.13–1.27; p = 0.02). No other significant differences in operative time, length of hospital stay, and wound healing time were found between the 2 groups. LIMITATIONS: This study was limited to the lack of double blinding and long-term follow-up in the included trials. CONCLUSIONS: Pursestring closure has significantly fewer surgical site infections and achieves better cosmetic outcomes following stoma reversal than conventional primary closure.